A contrastive analysis of semantic features of idiomatic expressions containing the word Money" in English and Vietnamese = Phân tích đối chiếu đặc điểm ngữ nghĩa của những thành ngữ có chứa từ “tiền” trong Tiếng Anh và Tiếng Việt . M.A Thesis Linguistics - Nguyễn, Thị Mai (University of Languages and International Studies, 2017)
48 p. + CD-ROM